Comparing Popular CNN Models for an Imbalanced Dataset of Dermoscopic Images - Tolan, Zafer; Duman, Erkan (Ali KARCI, 2021)
In this study, the performance of popular convolution architectures against an imbalanced dataset is analyzed in detail with a multi-classing medical image processing application. Our selection for dermoscopic images is a large-scale and imbalanced dataset consisting of 10,015 colored lesion images belonging to 7 different skin diseases, was used as a benchmark. Images without pathological testing are labeled by specialist dermatologists who are members of International Skin Imaging Association. The f1-score was preferred as the measurement metric during the training phase of the convolution networks, which were trained with imbalanced dataset, and the area under the receiver operating characteristic curve and the confusion matrix of each model were calculated at the test phase. In the validation phase of convolution networks, k-fold cross validation technique was used. In addition, the filters obtained from the ImageNet dataset have been imported with the Transfer-Learning option. Fine-tuning was applied to the deepest convolution layers in order for these pre-trained models to develop themselves specific to our application. In order to prevent the overfit problem, the feature extraction outputs of the models were drop-out at a rate of 50% after flattening, and L2-regularization (weigh decay) was applied during the update phase of the weights. Although it is not the main purpose of the study, in order to partially improve the performance of convolution architectures, synthetic lesion images created with data-augmentation for the minor classes in the imbalanced dataset were included in the training process in a way that does not cause information leakage.

Bu çalışmada, dengeli dağılım sergilemeyen bir veri seti karşısında popüler evrişimsel sinir ağı mimarilerinin nasıl bir performans sergileyebilecekleri çok-sınıflı bir medikal görüntü işleme uygulaması ile detaylı bir şekilde analiz edilmiştir. 7 farklı deri hastalığına ait 10.015 tane renkli lezyon resimlerinden oluşan büyük ölçekli ve dengesiz bir veri seti olan HAM10000(İnsan-Makineye Karşı-10000), test aracı olarak kullanılmıştır. Bu veri seti ile eğitilip performans karşılaştırması yapılan evrişimsel sinir ağı modellerinin eğitim aşamasında ölçüm metriği olarak f1-score değerleri ve test aşamasında ise her bir modelin hem hata matrisi hem de ROC eğrileri altında kalan AUC alanları hesaplanmıştır. Evrişimsel sinir ağı modellerinin eğitim süreçleri, k-fold çapraz doğrulama ile analiz edilmiştir. Ayrıca imagenet veri setindeki filtreler, Eğitim-Transferi seçeneği ile içe aktarılmıştır. Ön-eğitimli bu modellerin uygulamaya özgü kendilerini geliştirebilmeleri için ise en derindeki evrişim katmanlarına ince-ayar işlemi uygulanmıştır. Ezber yapma problemini engellemek amacı ile modellerin çıkardıkları özellikler, tek sütunlu vektör haline getirildikten sonra 50% oranında silme işlemi ve ağırlıkların güncelleme aşamasında ise L2-düzenleme(weigh decay) işlemi uygulanmıştır. Çalışmanın asıl amacı olmamak ile birlikte evrişim mimarilerin performanslarını kısmen de olsa iyileştirebilmek için HAM10000 sınıfındaki azınlık sınıfları için veri çeşitlendirme ile oluşturulan sentetik lezyon görüntüleri, bilgi sızıntısına neden olmayacak şekilde eğitim sürecine dâhil edilmiştir.
Dengeli Dağılım Sergilemeyen Dermoskopik Görüntü Veri Seti Üzerinde CNN Modelleri Karşılaştırma
Keywords: Artificial Intelligence; Yapay Zeka; Computer Software; Bilgisayar Yazılımı; Software Testing; Verification and Validation; Yazılım Testi; Doğrulama ve Validasyon